2010
DOI: 10.1117/1.3466580
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the metabolic deterioration of ex vivo skin from ischemic necrosis through the imaging of intracellular NAD(P)H by multiphoton tomography and fluorescence lifetime imaging microscopy

Abstract: Abstract. Ex vivo human skin has been used extensively for cosmeceutical and drug delivery studies, transplantable skin allografts, or skin flaps. However, it has a half-life of a few days due to ischemic necrosis. Traditional methods of assessing viability can be timeconsuming and provide limited metabolic information. Using multiphoton tomography and fluorescence lifetime imaging ͑MPT-FLIM͒ we assess ischemic necrosis of ex vivo skin by NAD͑P͒H autofluorescence intensity and fluorescence lifetime. Ex vivo sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 61 publications
(98 reference statements)
3
63
1
1
Order By: Relevance
“…As a result, NAD(P)H may be recruited by similar proteins related to oxidative repair, causing the lifetime change we observe in both solar-exposed skin and the liver after I/R injury. 33 Interestingly, these lifetime changes are in sharp contrast to ischemic necrosis and apoptosis, which are associated with a significant increase in the fluorescence lifetime of NAD(P)H. 11,34,35 While these processes also involve oxidative damage, the outcome is ultimately cell death and a breakdown of internal compartmentalization within the cell, 36 which may alter protein recruitment of NAD(P)H and thus result in the lifetime changes we observe. Further studies are required to identify the protein-binding associated changes for NAD(P)H in response to I/R injury and cell death.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…As a result, NAD(P)H may be recruited by similar proteins related to oxidative repair, causing the lifetime change we observe in both solar-exposed skin and the liver after I/R injury. 33 Interestingly, these lifetime changes are in sharp contrast to ischemic necrosis and apoptosis, which are associated with a significant increase in the fluorescence lifetime of NAD(P)H. 11,34,35 While these processes also involve oxidative damage, the outcome is ultimately cell death and a breakdown of internal compartmentalization within the cell, 36 which may alter protein recruitment of NAD(P)H and thus result in the lifetime changes we observe. Further studies are required to identify the protein-binding associated changes for NAD(P)H in response to I/R injury and cell death.…”
Section: Discussionmentioning
confidence: 73%
“…9 For example, autofluorescent nicotinamide adenine dinucleotide (NADH) is a direct measure of cellular metabolic state and can be used to study cellular damage. [10][11][12] The free and bound forms of NADH are involved in the anaerobic and aerobic production of adenosine triphosphate (ATP), respectively. 13,14 Accordingly, a change in the free/bound ratio gives insight into the metabolic state of a cell.…”
Section: Introductionmentioning
confidence: 99%
“…They can provide morphological and biochemical information about the skin by detecting auto fluorescence from endogenous skin fluorophores with little damage to the tissue, particularly with multiphoton tomography [127,128]. Similar imaging studies can also be carried out with freshly excised skin for short periods following excision [129]. Fluorescence lifetime imaging is used in conjunction with multiphoton tomography to provide information about the state or environment of a particular fluorophore, being useful in assessing the effects of physical treatments [130,131].…”
Section: In Vivomentioning
confidence: 99%
“…We have previously studied NAD(P)H in ischemic necrosis of the skin and showed that MPM-FLIM was useful for noninvasive imaging and to monitor the metabolic state of the skin. 11 Thus, the aim of this study was to investigate whether MPM and FLIM are useful tools in detecting disease progression in I/R injury, without the need for external markers.…”
Section: Introductionmentioning
confidence: 99%
“…9 The metabolic state can be determined in vivo through the recent advances in microscopy and the inherent fluorescent properties of NADH, as has been shown in assessing the viability of excised human skin stored under various conditions. 11,12 Multiphoton microscopy (MPM) has been utilized for the visualization of fluorescent molecules within the cell, 13 including measuring the absorption of nanoparticles into human skin. 14 MPM enables high-resolution imaging of physiology, morphology, and cell-cell interactions in live animals or intact tissue.…”
Section: Introductionmentioning
confidence: 99%